Community Empowerment to Improve the Village Economy through the Utilization of Tea Leaves in Bahbutong Village, Simalungun Regency - Siti Hajar; Fiqih Hasan Ashary; Aryo Hermawan; Nurkhay Rani; Indri Monika; Faiza Stevani (LPPM Universitas Muhammadiyah Tasikmalaya, 2021)
The community empowerment program is an activity that aims to increase the understanding and knowledge of the community in utilizing the existing potential. The level of understanding and knowledge of the community in Bahbutong Village is still limited in carrying out activities to utilize the potential of the village, this is related to the not optimal community empowerment efforts carried out. One of the potentials that can be pursued and reprocessed so as to get direct benefits that can be felt by the village community is tea leaves. So far, people only know that tea leaves are only for food and drink, so they have not been able to make a big contribution to the village economy. Utilization of tea leaves in Bahbutong Village can be an effort to improve the village economy through community empowerment activities carried out by the village government. The tea leaves in question are unused leaves or leftovers from tea plantations in Bahbutong Village. The method used in this research is the participatory rural appraisal (PRA) method. The results obtained in this study are new innovations in the use of tea leaves, namely the manufacture of tea aromatherapy candles that can provide relaxation for breathing and can also optimize community empowerment programs so that the village economy can increase